Poverty in the Indonesia-Malaysia border province (case study in West Kalimantan Province) - Pramushinta Arum Pynanjung; Edy Agustinus; Junaidi Junaidi; Rusli Burhansyah; Shenny Oktoriana (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2021)
This study aims to analyze the factors determining poverty in the Indonesia-Malaysia border province of West Kalimantan. Data were obtained from Statistics Indonesia (BPS) of West Kalimantan Province. From 2010 to 2019, panel data of regencies/cities in West Kalimantan were analyzed quantitatively. The results showed that the Random Equation Model (REM) using the GLS method was more appropriate for examining the impact of poverty in West Kalimantan. The study result found that Gross Regional Domestic Product, unemployment rate, and population density significantly affect poverty.